2012
DOI: 10.1002/ajhb.22251
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating weight and body image in the UAE: Strategies among young emirati women

Abstract: Obesity and overweight among young women in the Emirati population do not appear to be as significant a problem as they are in older populations. However, several other health-related causes for concern emerged in this study, including extreme dieting strategies, insufficient micronutrient and protein intake, and widespread inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We do note that there is, of course, extensive ethnographic and anthropological work (Anderson‐Fye, ; Bordo, ; Edmonds, ; McClure, ; Nichter, ; Reischer and Koo, ; Talukdar, ; Taylor, ; Trainer, ) focused on body projects, body image, and constructions of “bodies beautiful.” The obese body is a thread that winds through this literature, but more often it is focused on “normal” sized participants and obesity is framed as what a body should not be. We also do acknowledge, by way of redress, that there is a substantial body of “Fat Studies” research, one that prioritizes the voices and experiences of men and women who self‐identify as fat, and that typically has an overt political agenda of publicizing fat‐based discrimination and encouraging “acceptance and health at any size” attitudes (Atkins, ; Bombak, ; Dickens et al, ; Gailey, ; Rothblum and Solovay, ).…”
Section: The Challenges Of Meaningfully Measuring and Classifying Obementioning
confidence: 99%
See 1 more Smart Citation
“…We do note that there is, of course, extensive ethnographic and anthropological work (Anderson‐Fye, ; Bordo, ; Edmonds, ; McClure, ; Nichter, ; Reischer and Koo, ; Talukdar, ; Taylor, ; Trainer, ) focused on body projects, body image, and constructions of “bodies beautiful.” The obese body is a thread that winds through this literature, but more often it is focused on “normal” sized participants and obesity is framed as what a body should not be. We also do acknowledge, by way of redress, that there is a substantial body of “Fat Studies” research, one that prioritizes the voices and experiences of men and women who self‐identify as fat, and that typically has an overt political agenda of publicizing fat‐based discrimination and encouraging “acceptance and health at any size” attitudes (Atkins, ; Bombak, ; Dickens et al, ; Gailey, ; Rothblum and Solovay, ).…”
Section: The Challenges Of Meaningfully Measuring and Classifying Obementioning
confidence: 99%
“…Considerations of obesity in anthropology and allied social sciences have tended to be highly critical of medical and public health approaches, even to the point of questioning if “obesity” (clinically defined as registering a Body Mass Index (BMI) ≥30, see WHO, ) has any biological relevance at all. The topic of obesity is certainly an emotional public flashpoint in societies ranging from the US to Norway to the UAE (Farrell et al, 2011; Malterud and Ulriksen 2010; Trainer, ), with massive media and public health coverage in both traditional and social media outlets focusing on the so‐called “war on fat” (Campos, ; Greenhalgh, ; Saguy, ). For the most part, socioculturally‐oriented anthropologists and aligned social scientists (e.g., Boero, ; Braziel and LeBasco, ; Brewis et al, a, b; Casper and Moore, ; Greenhalgh, ; Kulick and Meneley, ; Rothblum and Solovay, ; Saguy, ) have focused on the social damage that results when obesity is defined as a “problem” in and of itself, in the absence of critical analyses of the cultural assumptions that undergird this perspective.…”
mentioning
confidence: 99%
“…In addition to physical inactivity and high consumption of sugar-laden and calorie-dense foods, it is suggested that the existing cultural values in some countries in favor of larger body size among women as a sign of healthiness, prestige, fertility, and/or wealth have a pivotal role in the higher prevalence of excess weight in women than in men [13]. Nevertheless, some other studies in this region have reported considerably high prevalence of body image dissatisfaction and ultra-thin body image ideals in the young female populations [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Third, some dynamic combination of wealth, poverty, income inequality, and upward mobility appear to be important. Based on participant observation and surveys of university students in the United Arab Emirates, Trainer () found that concerns around socioeconomic upward mobility (marriage and education) drive fat‐fear and pathological eating in ways that make it more difficult for young women to regulate their weight. Based on long‐term ethnographic work in Belize (2004, 2009), Anderson‐Fye proposes that participation in a transnational economy, drive for success in that new economy, and changing dietary options have introduced eating disturbance and awareness of body size and control among youth (both male and female, although more so for women).…”
mentioning
confidence: 99%
“…Third, some dynamic combination of wealth, poverty, income inequality, and upward mobility appear to be important. Based on participant observation and surveys of university students in the United Arab Emirates, Trainer (2012) found that concerns around socioeconomic upward mobility (marriage and education) drive fat-fear and pathological eating in ways that make it more difficult for young women to regulate their weight.…”
mentioning
confidence: 99%